XXVIII RUSSIAN NATIONAL CONGRESS “MAN AND MEDICINE”. COLLECTION OF ABSTRACTS. - article Editorial (Кардиоваскулярная терапия и профилактика)
XXVIII RUSSIAN NATIONAL CONGRESS “MAN AND MEDICINE”.COLLECTION OF ABSTRACTS.